Of Milk and Motherhood: The Kacaṅgalā Avadāna Read in a Brahmanical Light - Muldoon-Hules, Karen (Religions of South Asia, 2009)
When the story of Kacaṅgalā is borrowed from the Mūlasarvāstivādavinaya to the Avadānaśataka, a small but interesting Brahmanical literary trope is incorporated. That trope, which appears multiple times in parallel situations in Daṇḍin’s Daśakumāracarita, seems designed to bolster the claim that Kacaṅgalā, despite her present humble life, had been the mother of the being who would become Śākyamuni Buddha in 500 previous lives. This story is unknown in the southern Pāli sources, although a nun named Kajaṅgalā is mentioned in several places therein.